Neoadjuvant immunotherapy for lung cancer: current limitations and future prospects - Yang, Kunpeng; Wang, Lei; Wang, Zhe; Lv, Peiyun; Cai, Chenglun; Zhao, Hui; Sun, Wenjuan; Wang, Bao (Frontiers in Immunology, 2026)
Lung cancer is the leading cause of cancer-related mortality globally, with non-small cell lung cancer (NSCLC) accounting for the majority of cases. For resectable early-stage NSCLC, surgery and adjuvant chemotherapy remain the standard treatments, but the recurrence rate is high, and long-term survival outcomes are suboptimal. In recent years, immunotherapy, particularly immune checkpoint inhibitors (ICIs), has revolutionized the treatment of advanced NSCLC and is gradually being extended to early-stage disease. Neoadjuvant immunotherapy, as an emerging strategy, aims to activate anti-tumor immune responses preoperatively, eliminate microscopic metastases, and downstage tumors, thereby improving surgical resectability and enhancing long-term survival for patients. Several clinical trials have demonstrated that neoadjuvant immunotherapy, either alone or in combination with chemotherapy, significantly increases the major pathological response (MPR) and pathological complete response (pCR) rates, translating into improvements in event-free survival (EFS). However, this promising therapeutic approach faces numerous challenges, including the lack of precise biomarkers for efficacy prediction, unclear treatment strategies for patients with driver gene-positive tumors, primary and secondary resistance, management of immune-related adverse events (irAEs), and the complexities of post-treatment efficacy evaluation. This review aims to comprehensively summarize the latest clinical evidence on neoadjuvant immunotherapy for lung cancer, delve into the main challenges and opportunities encountered in clinical practice, and explore its future directions, including novel combination therapies, personalized treatment strategies, and the application of innovative technologies, with the goal of optimizing clinical management for early-stage lung cancer patients and advancing research in this field.